(3CSGSjGJ GdCYeGd aj Xd GdYhdeIs - (3aQjO eUWai(B, (3fgGds ((3GdGScfOQjI(B:s (3GdecJH GdLGeYj GdMOjK(B,s, 2006)
(3HjFI GdCYeGd(B: (3GdJYQja HefXeGJ GdCYeGd, bWGY GdCYeGd aj eUQ hGdNUNUI, GdeTQhYGJ GdUZjQI, GdCYeGd GdOhdjI, GdJLGQI GdGdcJQhfjI, GdJShjb(B: (3GdeHGOF hGdeaGgje GdCSGSjI(B: (3Sdhc GdeSJgdc, GdGfJGL hGOGQI GdYedjGJ, GOGQI GdehGQO GdHTQjI, GdTQGA, CSGSjGJ GdJehjd, fXe hJcfhdhLjG GdeYdheGJ, GOGQI QCS GdeGd GdYGed(B.s
(3GdeQGLY U(B.409s
Keywords: (3EOGQI GdCYeGd(B- (3GdYhdeIs; (3GdJShjbs; (3GdehGQO GdHTQjIs; (3JcfhdhLjG GdeYdheGJs